2020
DOI: 10.3389/fphar.2020.00306
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of NLRP3 Inflammasome by Erythropoietin via the EPOR/JAK2/STAT3 Pathway Contributes to Attenuation of Acute Lung Injury in Mice

Abstract: Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are common and devastating clinical disorders with high mortality and no specific therapy. An excessive inflammatory response results in the progression of ALI/ARDS, and the NLRP3 inflammasome is a key participant in inflammation. Erythropoietin (EPO), which is clinically used for anemia, reportedly exerts pleiotropic effects in ALI. However, whether EPO could protect against lipopolysaccharide (LPS)-induced ALI by regulating the NLRP3 infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 50 publications
(50 reference statements)
2
48
0
Order By: Relevance
“…Secondly, NLRP3 among inflammasome components is well known to various kidney disease including IR-AKI. The protective effect of EPO on AKI is very well-described; however, it is not for inflammasome, even reported in acute lung injury [34]. According to our data, EPO significantly decreased the expression levels of the inflammasome-related factors NLRP1, NLRP3, and cleaved caspase-1.…”
Section: Discussionsupporting
confidence: 50%
“…Secondly, NLRP3 among inflammasome components is well known to various kidney disease including IR-AKI. The protective effect of EPO on AKI is very well-described; however, it is not for inflammasome, even reported in acute lung injury [34]. According to our data, EPO significantly decreased the expression levels of the inflammasome-related factors NLRP1, NLRP3, and cleaved caspase-1.…”
Section: Discussionsupporting
confidence: 50%
“…We used siRNA-lncRNA4344 and observed that interference with lncRNA4344 increased the expression of NLRP3 and LPS-induced IL-18 and IL-1β production, which is considered a critical role in early ALI. 35 , 36 Western Blot results also confirmed the NLRP3 and Caspase-1 expression levels were decreased under siRNA-lncRNA4344 conditions. We proposed that therapy targeting lncRNAs related to ceRNA regulatory mechanisms may provide a different direction for ALI/ARDS treatment.…”
Section: Resultsmentioning
confidence: 63%
“…The first clinical study for a NLRP3 inflammasome inhibitor (Tranilast) to treat COVID-19 is ongoing and registered in the Chinese clinical trial registry ( 45 ). Other studies are still in a pre-clinical phase and study the effect on acute lung injury or on cell lines for example with resveratrol ( 46 ), tetracycline ( 47 ) or erythropoietin ( 48 ) or nicardipine, a L-type calcium antagonist ( 49 ), lidocaine ( 50 ) CP-456,773 ( 51 ), Diacerein ( 52 ). For colchicine it is hypothesized that it has an effect on NLRP3-mediated diseases ( 53 ).…”
Section: Treatment Optionsmentioning
confidence: 99%